DNA origami applications in cancer therapy - Udomprasert, Anuttara (Cancer Sci, 2017)
Due to the complexity and heterogeneity of cancer, the development of cancer diagnosis and therapy is still progressing, and a complete understanding of cancer biology remains elusive. Recently, cancer nanomedicine has gained much interest as a promising diagnostic and therapeutic strategy, as a wide range of nanomaterials possess unique physical properties that can render drug delivery systems safer and more effective. Also, targeted drug delivery and precision medicine have now become a new paradigm in cancer therapy. With nanocarriers, chemotherapeutic drugs could be directly delivered into target cancer cells, resulting in enhanced efficiency with fewer side‐effects. DNA, a biomolecule with molecular self‐assembly properties, has emerged as a versatile nanomaterial to construct multifunctional platforms; DNA nanostructures can be modified with functional groups to improve their utilities as biosensors or drug carriers. Such applications have become possible with the advent of the scaffolded DNA origami method. This breakthrough technique in structural DNA nanotechnology provides an easier and faster way to construct DNA nanostructures with various shapes. Several experiments proved that DNA origami nanostructures possess abilities to enhance efficacies of chemotherapy, reduce adverse side‐effects, and even circumvent drug resistance. Here, we highlight the principles of the DNA origami technique and its applications in cancer therapeutics and discuss current challenges and opportunities to improve cancer detection and targeted drug delivery.